The importance of the New Silk Road for the development of rural and municipal commune of Terespol - Bereziński, Stanisław (Turystyka i Rozwój Regionalny, 2022)
One of the key factor for local development is an advantageous localization in terms of transportation, especially along or on the crossroads of major transport corridors. One of such corridor on the Eurasian continent is the New Silk Road which crosses Polish-Belarusian border in Terespol, where in Małaszewicze complex of intermodal terminals is located. The aim of this study was to verify the impact of this corridor on the evolution of the TFL sector in the Terespol rural and municipal communes in relation to theirs socio-economic growth. Conducted analysis confirmed sings of that the New Silk Road may be consider as a driving force for development in local scale.